EKSISTENSI BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM MENANGANI TAKE OVER MOBIL SECARA ANGSURAN - Febrianti, Resha; Adawiyah, Rabiatul; Nurani, Muhammad Fahmi; Hidayatullah, Muhammad Syarif (Borneo Law Review, 2023)
AbstractInteresting problem in this study discuss settlement efforts default if the collateralobject has been transferred to a third party. Associated with way of guaranteeing inthe a motor vehicle financing agreement, it is inseparable from possible risks that mayoccur, such as take over to a third party without creditor’s knowledge. This study aimsto identify and analyse the role and constraints of the Consumer Dispute ResolutionAgency (BPSK) in handling car take over instalments (analysis of decision number06/PT/BPSK.BJM/IV/2022). This type of research uses qualitative methods with caseresearch (study case). The object of this research in the office staff of the ConsumerDispute Resolution Agency (BPSK) City of Banjarmasin. The data sources used areinterview results and secondary data. Then do the analysis to draw conclusion. Theresult of this study indicate that in carrying out its duties and authorities the role ofthe Consumer Dispute Resolution Agency (BPSK) is towards efforts legal protectionregarding car take over in Decision Number 6/PT/BPSK.BJM/IV/2022 is to act as anassembly that decides disputes, the parties submit their settlement to the ConsumerDispute Resolution Agency (BPSK) because the parties to the dispute resolution chooseusing the arbitration method. Consumer Dispute Resolution Agency (BPSK)constrained to help resolve the case in the event that the BPKB cannot taken becausethe debtor cannot show the original identity of the power of attorney for taking BPKB ,so naturally the creditor has not submitted it. Based on this, the role of the ConsumerDispute Resolution Agency (BPSK) in carrying out its duties and authorities has actedin accordance with the provisions applicable law, and become a fair and objective arbiter in protecting consumer rights. Presence of the of the Consumer Dispute Resolution Agency (BPSK) provide protection and guarantees for consumer in conducting transactions financing, as well as facilitating efficient and fair dispute resolution.Keywords: Consumer Dispute Resolution Agency (BPSK); take over; installmentAbstrak Permasalahan menarik dalam penelitian ini membahas upaya penyelesaian wanprestasi apabila objek jaminan sudah berpindah ke pihak ketiga. Berkaitandengan cara penjaminan dalam perjanjian pembiayaan kendaraan bermotor, tidakterlepas dari kemungkinan risiko yang terjadi, seperti take over kepada pihak ketigatanpa sepengetahuan kreditur. Penelitian ini bertujuan untuk mengetahui danmenganalisis peran dan kendala Badan Penyelesaian Sengketa Konsumen (BPSK)dalam menangani take over mobil secara angsuran (analisa putusan nomor06/PT/BPSK.BJM/IV/2022). Jenis penelitian ini menggunakan metode kualitatifdengan penelitian kasus (case study). Objek penelitian ini adalah pegawai kantorBadan Penyelesaian Sengketa Konsumen (BPSK) Kota Banjarmasin. Adapun sumberdata yang digunakan adalah hasil wawancara dan data sekunder. Kemudiandilakukan analisis untuk menarik kesimpulan. Hasil penelitian ini menunjukkanbahwa dalam menjalankan tugas dan wewenangnya peran Badan PenyelesaianSengketa Konsumen (BPSK) terhadap upaya perlindungan hukum mengenai take overmobil pada putusan Putusan Nomor 6/PN-BPSK.BJM/IV/2022 adalah bertindaksebagai majelis yang memutuskan sengketa, para pihak menyerahkanpenyelesaiannya kepada Badan Penyelesaian Sengketa Konsumen (BPSK) karena parapihak dalam penyelesaian sengketa memilih menggunakan metode arbitrase. BadanPenyelesaian Sengketa Konsumen (BPSK) terkendala membantu menyelesaikanperkara tersebut dalam hal BPKB tidak bisa diambil disebabkan debitur tidak dapatmenunjukkan identitas asli pemberi kuasa untuk pengambilan BPKB, sehingga wajarkreditur belum menyerahkannya. Berdasarkan hal tersebut peran Badan PenyelesaianSengketa Konsumen (BPSK) dalam menjalankan tugas dan wewenangnya sudahbertindak sesuai dengan ketentuan yang berlaku, dan menjadi penengah yang adilserta objektif dalam melindungi hak-hak konsumen. Kehadiran Badan PenyelesaianSengekta Konsumen (BPSK) memberikan perlindungan dan jaminan bagi konsumendalam melakukan transaksi pembiayaan, serta memfasilitasi penyelesaian sengketayang efisien dan adil.